2019
DOI: 10.7717/peerj.6697
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of mouse liver in response to DENV-1 infection by deep sequencing

Abstract: Background Dengue caused by dengue virus (DENV) serotypes −1 to −4 is the most important mosquito-borne viral disease in the tropical and sub-tropical countries worldwide. Yet many of the pathophysiological mechanisms of host responses during DENV infection remain largely unknown and incompletely understood. Methods Using a mouse model, the miRNA expressions in liver during DENV-1 infection was investigated using high throughput miRNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…MiRNAs are small non-coding RNA molecules that can regulate gene expression by inhibiting messenger RNA (mRNA) translation or inducing mRNA degradation[ 17 ]. Recently, Pong et al reported that, with a DENV-1 infection, 23 highly differentially expressed miRNAs jointly modulate the adaptive immune response involving TGF-β, MAPK, PI3K-Akt, Rap1, Wnt, and Ras signalling pathways[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small non-coding RNA molecules that can regulate gene expression by inhibiting messenger RNA (mRNA) translation or inducing mRNA degradation[ 17 ]. Recently, Pong et al reported that, with a DENV-1 infection, 23 highly differentially expressed miRNAs jointly modulate the adaptive immune response involving TGF-β, MAPK, PI3K-Akt, Rap1, Wnt, and Ras signalling pathways[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expressions of miR-24-1-5p, miR-512-5p, and miR-4640-3p were able to distinguish mild dengue from those with liver complications. At the same time, miR-383 was significantly more expressed in dengue with mild clinical status than those diagnosed with severe dengue and accumulation of body fluids [40,41].…”
Section: Mirna Impact On Denv Infectionmentioning
confidence: 89%
“… 19 Differentially expressed miRNAs are detected in the sera of dengue patients and in DENV-infected mice, some of which may be used as indicators for dengue severity. 20 , 21 , 22 Moreover, a broader role for DENV infection in miRNA modulation has been documented. Infection of human hepatoma cells with DENV results in decreased mRNA levels of miRNA processing proteins, including Dicer, Drosha, Ago1, and Ago2, and subsequent downregulation of miRNAs.…”
Section: Introductionmentioning
confidence: 99%